170k views
0 votes
Solving multi step equation
6=-3(x+2)

2 Answers

7 votes
6=-3x-6
6+6=-3x
12=-3x
X=-4
User Herb Sutter
by
5.2k points
1 vote

Answer:

x=-4

Explanation:

Start by distributing the -3 to both x and 2 (This is called the distributive property)

After using the distributive property your equation should look like this:

6=-3x-6

Now add 6 to both sides! Your equation should now look like this:

12=-3x

Now divide both sides by -3! Your equation should now look like this:

-4=x

You can rearrange -4=x to x=-4 as your final answer!

User Geoff Davids
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.